Helical folding in heterogeneous foldamers without inter-residual backbone hydrogen-bonding - Priya, Gowri; Kotmale, Amol S.; Gawade, Rupesh L.; Mishra, Deepti; Pal, Sourav; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
This communication describes a set of hybrid foldamers that do not feature inter-residual, but intra-residual backbone hydrogen-bonding, yet adopt a preferentially folded conformation displaying right-handed helical architecture. Conformational ordering is apparently due to the combined conformational restrictions imposed by the conformationally restricted individual amino acid residues with which the oligomers are made of.

Highly concise and practical route to clavaminols, sphinganine and (+)-spisulosine via indium mediated allylation of alpha-hydrazino aldehyde and a theoretical insight into the stereochemical aspects of the reaction - Pandey, Menaka; Chowdhury, Partha Sarathi; Dutta, Achintya Kumar; Kumar, Pradeep; Pal, Sourav (RSC Advances, 2013)
A conceptually different approach has been employed for the synthesis of 1,2-amino alcohols by proline-catalyzed alpha-amination of aldehyde and one-pot indium mediated allylation of the crude alpha-hydrazino aldehydes. DFT based quantum chemical calculations have been performed to obtain a quantitative explanation of the stereoselectivity of the reaction.

Hydrogen atom chemisorbed gold clusters as highly active catalysts for oxygen activation and co oxidation - Manzoor, Dar; Pal, Sourav (Journal of Physical Chemistry C, 2014)
Using oxygen activation and carbon monoxide oxidation as a probe, we have carried out density functional theory (DFT) calculations to investigate the effect of hydrogen atom chemisorption on the reactivity and catalytic activity of gold nanoclusters. In the present work, we particularly focus on the closed shell neutral Au-n (n = 2, 4, 6, 8) gold clusters which are reported to be chemically inert and catalytically less active. The results confirm that the hydrogen atom chemisorption activates the inert clusters, thereby leading to enhanced binding and activation of the O-2 molecule. A significant amount of increase in the O-O and decrease in the Au-O bond lengths together with a pertinent red shift in the O-O stretching frequencies clearly indicates the stronger binding and activation of oxygen molecule in the case of AunH clusters. Further, our results reveal that the hydrogen atom chemisorbed gold clusters are catalytically more active with low activation barriers for the CO oxidation reaction compared to the parent less active closed shell gold clusters. Thus, in short the current theoretical observation provides key inputs for enhancing the reactivity and catalytic activity of inert gold clusters through the adsorption of a small atom or a molecule.

Hydrogen adsorption in ZIF-7: A DFT and ab-initio molecular dynamics study - Dixit, Mudit; Major, Dan Thomas; Pal, Sourav (Chemical Physics Letters, 2016)
Primary H-2 adsorption sites in a zeolitic imidazolate framework, ZIF-7, are identified using ab-initio density functional theory (DFT) based molecular dynamics annealing simulations. The simulations suggest several low energy adsorption sites. The effect of light transition metal decoration on hydrogen storage properties was studied. Our ab-intio DFT calculations illustrate that decorating the ZIF with Sc increases both the number of H-2 molecules, as well as the H-2 binding energy. The binding energy (similar to 25 kJ/mol per H-2) at 8H(2) loading in the pore, suggests that Sc-ZIFs can be potential candidates for hydrogen storage. (C) 2016 Elsevier B.V. All rights reserved.